Collective Clan Disease among the Nanay - Bulgakova, Tatiana D. (Journal of Northern Studies, 2010)
According to Nanay emic ideas, shamanic disease, which affects a shaman in the period of his or her formation, also affects his or her relatives, who begin to suffer from nervous disorders and other problems but recover at their new shaman’s incarnation. A similar spiritual correlation within the group of relatives becomes apparent also when a shaman is involved in a situation which connects him or her with the spiritual world (murder, death, incest, etc.), so that the consequences of such events influence not only the shaman, but also his or her kin. From the emic perspective, relations with the spirits have not only spiritual, but also biological components (emerging for instance, in the idea about the possibility of human-spiritual cohabitation), which opens up possibilities for spirituality to be inherited by descendants. These circumstances suggest that the social factors that unite the clan (exogamy etc.), are secondary to the religious factors, and probably used as a means to adapt to the spiritual problems that shamanists face. Running the danger of collective clan disease, people have to remember their clan peculiarity and exclusiveness and undertake common efforts for its avoidance. Being aware of their patrilineal descent and of their own place in it, people can define the circle of possible persons who are subject to similar mental and other troubles and who should look together for the means of a cure. The wish to ensure spiritual security results in the social prescriptions and taboos that form the patrilineal clan.